Rancang Bangun Sepeda Listrik 250 Watt Dengan Mengukur Kecepatan Dan Daya Baterai - Miftachul Ulum; Mutiara Hikmah; Achmad Fiqhi Ibaidillah; Kunto Aji Wibisono (Universitas Darul Ulum, 2021)
Electric bicycles are one of many vehicles with alternative fuels. This electric bike uses electric power as its power source. Whose electrical energy is converted into motion energy. To convert that electrical energy into motion energy is needed which is called an electric dynamo. The electric dynamo here becomes an engine core on an electric bike. The performance of electric bicycles is measured based on high power efficiency, low energy consumption levels and stable electric bicycle components in their use. To monitor the performance, a speed and battery power scrolling system was designed on a 250W electric bike. An electric motorcycle is a type of vehicle consisting of brushless direct current (BLDC) to move the wheel, controller as energy flow regulator on BLDC, and battery as a power source. The main parts of this monitoring system include two 12 volt batteries in the series, controller, BLDC, throttle, proximity sensor, liquid crystal display (LCD). Throttle works as a BLDC speed controller. DC power meter as a measuring detector for the amount of electric current, electrical voltage, electrical energy, and electrical power displayed on the LCD.